Demokrasi Jokowian dan Kepemimpinan Transformasional - Boni Hargens; Richard G Mayopu (PAX HUMANA, 2015)
Politics as a symbolic system had been provided space for analysts to contribute their argument. Very diverse symbolic Systems has different interpretations. Therefore, this paper is concern to see the symbol in Christianity is actually more complex when associated with Christian leadership. Challenges and obstacles also come off in form of political communication in the form of distortion that is built on the basis of Christian leadership. Jokowian which is the introduction of a new model of leadership to the Indonesian context is also available as an answer to the question of how leadership can be embedded in the soul of Christian leaders in Indonesia?. And that is the spirit of transformational leadership. Keywords: Symbol, Distortion, and Transformational leadership.